2003
DOI: 10.1200/jco.2003.01.062
|View full text |Cite
|
Sign up to set email alerts
|

Older Age Is an Adverse Prognostic Factor in Stage I, Favorable Histology Wilms’ Tumor Treated With Vincristine Monochemotherapy: A Study by the United Kingdom Children’s Cancer Study Group, Wilm’s Tumor Working Group

Abstract: Treatment for stage I FH Wilms' tumor is generally successful using vincristine monotherapy after immediate nephrectomy, and therefore, the risks of dactinomycin hepatopathy can be avoided. However, age at least 4 years is a significant adverse prognostic factor. This treatment schedule should be considered in any trial of treatment reduction in very young children with stage I FH Wilms' tumor, regardless of tumor size, and we suggest that the upper age limit for the reduced therapy be set at 4 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 18 publications
3
59
0
1
Order By: Relevance
“…Cooperative studies have shown that increasing age is associated with an increased risk of recurrence of nonmetastatic WT (6,7,(9)(10)(11). This is only partly explained by the fact that the occurrence of anaplasia increases with age (12); even in patients with favorable histology, older age seems to be associated with less favorable outcome.…”
Section: Generalmentioning
confidence: 99%
See 2 more Smart Citations
“…Cooperative studies have shown that increasing age is associated with an increased risk of recurrence of nonmetastatic WT (6,7,(9)(10)(11). This is only partly explained by the fact that the occurrence of anaplasia increases with age (12); even in patients with favorable histology, older age seems to be associated with less favorable outcome.…”
Section: Generalmentioning
confidence: 99%
“…Anaplasia is only very rarely seen in WT diagnosed during the first year of life and is also rare in the second year of life (12). Nevertheless, even in the group of patients with favorable histology, older age seems to be correlated with a higher risk of relapse and death, although prognostic factors such as stage or histology seem to be more powerful (7). Other suggested reasons for the adverse survival rates in older children are delay in diagnosis, advanced tumor stage at presentation, and intrinsically different biological behaviors (7).…”
Section: Age In Correlation With Other Prognostic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cooperative group studies have shown that increasing patient age is associated with increased risk of recurrence in nonmetastatic Wilms' tumor [14][15][16][17]. A subgroup with an outstanding prognosis are patients less than 2 years of age with small (<550 g) stage I favorable histology tumors [18][19][20].…”
Section: Patient Agementioning
confidence: 99%
“…Also, in a study by Pritchard-Jones, it was shown that older children (> 4 years) are at increased risk of recurrence (p = 0.001) [9]. In that study, 242 patients with stage I tumors and favorable histopathology were studied.…”
Section: Discussionmentioning
confidence: 99%